Legal Protection for Victims of Sexual Violence Evaluation of the Implementation of the Law on Sexual Violence Crimes - Lambang, Raden Bimo Dwi; Wahyuningsih, Sri Endah (Jurnal Hukum Khaira Ummah, 2025)
Criminal acts of sexual violence are increasing in Indonesia. This crime is very detrimental to the victims because of the impacts it causes. Victims must receive protection for their rights as regulated in Law Number 12 of 2022, however, protection for the rights of victims of sexual violence has not been optimal due to weaknesses in terms of legal substance and legal culture. This study uses a constructivism paradigm, with a socio-legal research approach method. The specifications of this study are descriptive analytical. The data used are primary data and secondary data, which are then analyzed qualitatively. The results of the study show that: 1. Victim protection can also include abstract (indirect) and concrete (direct) forms of protection: (1) Abstract protection is basically a form of protection that can only be enjoyed or felt emotionally (psychically), such as satisfaction (satisfaction); (2) Concrete protection is basically a form of protection that can be enjoyed in real terms, such as the provision of material or non-material. 2. Implications of the Regulation of Legal Protection for Victims of Sexual Violence Based on Law Number 12 of 2022, there are weaknesses in the protection of victims' rights, in terms of: (1) legal substance, namely: (i) not all forms of sexual violence are regulated in Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, (ii) Law Number 12 of 2022 opens up space for subsidiary punishment or substitute punishment for perpetrators in the mechanism for providing restitution to victims, and (iii) overlapping laws and regulations governing sexual violence; (2) legal culture, namely: (i) law enforcement, (ii) society. 3. Legal Protection for Women Resulting from Criminal Acts of Sexual Violence: (1) Based on the laws and regulations in Indonesia, there are various regulations that regulate forms of sexual violence such as the 1945 Constitution, Law Number 1 of 1946 concerning the Criminal Code, Law Number 39 of 1999 concerning Human Rights, Law Number 26 of 2000 concerning the Human Rights Court, Law Number 23 of 2004 concerning the Elimination of Domestic Violence, Law Number 21 of 2007 concerning the Eradication of Criminal Acts of Human Trafficking, Law Number 35 of 2014 Amendment to Law Number 23 of 2002 concerning Child Protection, Law Number 17 of 2016 which stipulates the State Regulation in Lieu of Law Number 1 of 2016 concerning the second amendment to Law Number 23 of 2002 concerning Child Protection has become a Law, Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, Law Number 1 of 2023 concerning the Criminal Code and Law Number 17 of 2023 concerning Health. (2) Efforts to prevent sexual violence, including: a. The role of the government, b. The role of society, c. The role of the family and d. The role of oneself.